Implementación de un sistema de costos por proceso para determinar la rentabilidad en la industria textilera “BorDisGraf” del cantón Guaranda, provincia Bolívar, en el año 2022. - Patín Rea, Marco Antonio (2023)
This research project is about the "Implementation of a system of costs per process to determine the profitability in the "BorDisGraf" industry of the Guaranda canton, Bolívar province, in the year 2022". Industrial companies today demand profitable and timely information that allows safe decisions to be made, as an industrial company, you need to understand the manufacturing process, why the design of the process cost system is essential, since it will facilitate this process and optimize resources for better decision making. The methodology used during the project investigation was field, bibliographic, or documentary research and descriptive research, using data collection techniques, observation, survey, and interview. Carrying out an analysis and later the interpretation of all the information collected, for this purpose the need to implement a process cost system design adapted to the characteristics of the industry was determined. In conclusion, a process costing system is an important tool because it allows the unit cost of a product to be accurately determined and the costs of these elements to be obtained at each stage of the production process, with adequate control of the costs of raw materials, labor direct labor and indirect manufacturing costs, with the design of the process cost system implemented in the industry will help measure the profitability of the industry.